(untitled) (Journal of Dhaka Medical College, 2010)
Context: Diabetic retinopathy is a major cause of ocular morbidity among the diabetic patient. The aim of this study is to establish that hyperlipidaemia contributes to the development of diabetic retinopathy. Method: A cross sectional observational Study of 140 consecutive patients of Non insulin dependent diabetis mellitus more then 05 years were included in the study. Results: 140 NIDDM paticnts and 50 non diabetic control persons. were included in the study. In this study mean serum total cholesterol was 272.33 mg / dl, 187.70 mg /dl and 132.56 mg /dl respectively. Among the 3 study groups, 58.9% was diabetic retinopathy patients, 56% patients without retinopathy and 54% in non- diabetic controls. Visual acuity was 0.34, 0.08 and 0.06 respectively. Conclusion: This study suggests that diabetic retiopathy patients need assessment of serum lipids and they may need lipid-lowering agent to halt the progression of diabetic retinopathy and also to protect the patients from systemic morbidity of hyperlipidaemia. Key words: Hyperlipidaemia; Diabetic Retinopathy DOI: 10.3329/jdmc.v17i2.6584 J Dhaka Med Coll. 2008; 17(2) : 62-66